Pengaruh Budget Participation Terhadap Managerial Performance Melalui Procedural Fairness Sebagai Variabel Intervening - Eduardus - Hartono; Josua - Tarigan (Business Accounting Review, 2016)
Companies are faced with the pressures of globalization that requires new management strategic plan to maintain business organization. In Surabaya City, the competitiveness of business development is quite high, according to Surabaya city website as saying that Surabaya became the center of business and trade activities. One management technique that can be used is the budget. In preparing a budget, communication is needed between supervisors and subordinates to inform each other. Therefore, it is necessary to have participation in the making of a budget.This study aimed to examine the influence of budget participation to managerial performance through procedural fairness as an intervening variable. The type of data in this research was quantitative; the source of the data used was primary data. Data were collected by spreading questionnaires. This research using 135 samples consisting of 45 companies located in the region of Surabaya and around Surabaya with 3 respondents who have positions as manager. The hypotheses in this study were tested using the software Partial Least Square (PLS). Budget participation showed the affect on procedural fairness and managerial performance.